Stress, Anxiety, and Depression and Their Related Factors Among Dental Students: A Cross-Sectional Study from Southeast of Iran - Molouk Torabi Parizi; Jahangir Haghani; Mahsa Mahdian; Sara Amanpour; Maryam Raoof; Niloofar Shadman (Kerman University of Medical Sciences, 2019)
Background Dental students are exposed to various stressors that are related to treatment procedures, training, and administrative challenges in the college. Objectives The aim of this study was to assess the stress, anxiety, and depression levels of dental students and their relationships with demographic factors. Methods This was a descriptive-analytical cross-sectional study on 297 dental students enrolled at the Kerman University of Medical Science in 2015 - 2016. The stress, anxiety, and depression levels were measured using the depression anxiety stress scale-21 (DASS-21). Data on demographic characteristics were also obtained. The statistical analysis was carried out by SPSS (version 11.0) using the chi-squared test. P < 0.05 was set as the level of significance. Results The mean age of the participants was 23.80 ± 1.2 years; 58.9% were female, 88.9% were married, and 33.7% were dormitory students. Free education was provided for 64% of the students while the others were charged a tuition fee. The prevalence rates of moderate to extremely severe levels of stress, anxiety, and depression were 39.7%, 39.4%, and 35.7%, respectively. Stress, anxiety, and depression were not significantly associated with the year of academic study, gender, marital status, and place of residence (P > 0.05). The students with higher scores in the entrance exam who were free of charge presented significantly higher levels of severe-to-extremely severe stress and depression (P = 0.003 and P = 0.033, respectively) than students who were charged tuition fees. Conclusions Based on the findings of the present study, the high prevalence of depression, anxiety, and stress among dental students in Kerman is alarming. This emphasizes the need for interventions, with the development of appropriate support services for this group. However, further studies should be conducted to find major sources of depression, anxiety, and stress.